PENGEMBANGAN MEDIA PEMBELAJARAN KARTU PERTOLONGAN DAN TANTANGAN PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS IV SDN 09 KOTO BARU - Susilawati, Wiwik Okta; Apreasta , Lika; Ririn, Ririn Aprilia Zurni; Sari, Ayu Mustika; Anggrayni, M. (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
This study aims to develop a learning media in the form of help and challenge cards for the subject of Pancasila Education for fourth-grade students at SDN 09 Koto Baru. This media is designed using the 4-D model, which includes the stages of defining, designing, developing, and disseminating. The validity of the media was tested by three validators, including lecturers and education practitioners, with highly valid results in terms of graphics, content/material, and language. Practicality tests showed that this media is very practical, with a 100% positive response from teachers and students. The effectiveness of the media was tested through learning outcome tests, showing a completion rate of 89.47%, with 17 out of 19 students meeting the criteria. The results of this study indicate that the